Gateways to understanding music - Rice, Timothy, 1945-; Wilson, Dave (David R.), 1980- (Routledge, imprint of the Taylor & Francis Group, 2023)
"Preface to the second edition. Gateways to Understanding Music is designed for introductory music appreciation and music history courses dedicated to the principles of diversity, equity, and inclusion. ... In this book we ratain the historical approach of most textbooks that serve these kinds of courses, but we decenter European classical music, placed it in an equitable relationship to all the other kinds of music that contribute to musical and cultural life today."--Page xx, preface.